Wet-process material mixing mode and method for preparing composite graphite bipolar plate by using wet-process material mixing mode

Through the combination of wet mixing technology and a combination of a variety of high-quality raw materials, the problems of poor mixing uniformity, dust pollution and insufficient adhesion in the preparation of composite graphite bipolar plates are solved, and efficient and environmentally friendly bipolar plate preparation is achieved, which significantly improves its performance and stability.

CN119695186APending Publication Date: 2025-03-25XIANGTAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411863879.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing composite graphite bipolar plate preparation process has problems such as poor mixing uniformity, serious dust pollution and insufficient adhesion. Nanomaterials are prone to agglomeration during the mixing process, which affects their dispersion properties.

Method used

Wet mixing technology is used to achieve efficient dispersion and uniform distribution of nanomaterials through liquid phase medium and ultrasonic methods. Combined with materials such as scale graphite, worm graphite, synthetic resin and coupling agent, high-performance composite graphite bipolar plates are prepared.

Benefits of technology

It significantly improves the conductivity, thermal conductivity and mechanical properties of the bipolar plate, reduces dust pollution and production costs, and improves the stability and reliability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695186A_ABST
    Figure CN119695186A_ABST
Patent Text Reader

Abstract

The invention relates to the field of fuel cells, in particular to a raw material method for preparing and pressing a composite graphite bipolar plate by adopting wet mixing. The composite graphite bipolar plate plays an important role in a fuel cell and is mainly used for conducting electricity, distributing reaction gas, draining water and supporting a cell structure. A dry mixing process in the prior art has the problems of non-uniform mixing, dust pollution, insufficient binding power and the like, so that the conductivity, the mechanical property and the durability of the bipolar plate are influenced. In order to overcome the problems, a wet mixing process is adopted, the combination effect among the components is improved through a liquid-phase medium, and particularly, the method has remarkable advantages in dispersion of nano materials (such as carbon nanotubes). The uniformity of the material can be improved by wet mixing, the binding force between the nano material and the graphite particles and the binding agent is enhanced, and the electrical conductivity, the thermal conductivity, the mechanical strength and the corrosion resistance of the composite graphite bipolar plate are further improved. In addition, the invention also provides a preparation method of the fuel cell graphite composite bipolar plate with low energy consumption and high efficiency, the production efficiency is obviously improved, and the environmental pollution is reduced. The method can optimize the performance of the graphite composite bipolar plate, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fuel cells, and in particular to a method for preparing raw materials for pressing composite graphite bipolar plates by wet mixing. Background Art

[0002] Fuel cells, as a clean and efficient energy conversion device, have broad application prospects. Bipolar plates are an important component of fuel cells. Their main functions are to conduct electricity, distribute reaction gases, drain water, and support the battery structure. Composite graphite bipolar plates have become one of the mainstream materials for fuel cell bipolar plates due to their excellent conductivity, good corrosion resistance, and low production cost.

[0003] At present, the preparation of composite graphite bipolar plates usually adopts the dry mixing process, which is to physically mix graphite, adhesives and other fillers and then perform compression molding. However, the traditional dry mixing process has the following problems:

[0004] 1. Poor mixing uniformity: Due to the differences in particle size and density between the components, it is easy to cause uneven mixing, which affects the conductivity and mechanical properties of the bipolar plate.

[0005] 2. Serious dust pollution: A large amount of dust is easily generated during the dry mixing process, which is not only unfriendly to the environment, but also may cause harm to the health of production personnel.

[0006] 3. Insufficient bonding: The adhesive is not tightly bonded to the graphite particles, which may affect the density and durability of the bipolar plate.

[0007] In recent years, nanomaterials such as conductive carbon black, carbon nanotubes and graphene have been widely used in composite materials due to their excellent physical and chemical properties to enhance conductivity and mechanical properties. However, due to their large specific surface area and high surface energy, these nanomaterials are prone to agglomeration during the mixing process, which limits their dispersion performance and thus affects their enhancement effect.

[0008] Wet mixing technology uses liquid as a medium to improve the bonding effect between components through chemical or physical effects, especially showing significant advantages in the dispersion of nanomaterials:

[0009] 1. Improve the agglomeration problem: Liquid media can reduce the surface tension of nanomaterials. Through the action of ultrasound, stirring or chemical dispersants, efficient dispersion of materials such as conductive carbon black, carbon nanotubes and graphene can be achieved.

[0010] 2. Enhance interfacial bonding: Nanomaterials can better contact with graphite particles and binders in wet mixing, improve interfacial bonding, and thus enhance the mechanical strength and conductive properties of the composite material.

[0011] 3. Optimize material uniformity: Wet mixing can achieve uniform mixing of various components through the high fluidity of the liquid phase, especially for the uniform distribution of micron-sized graphite and nanomaterials.

[0012] 4. Improve preparation efficiency: By optimizing the dispersion state of nanomaterials, the amount of materials used can be significantly reduced, while achieving performance improvements and further reducing production costs.

[0013] Therefore, developing a preparation method based on wet mixing technology can not only solve the dust pollution and uneven mixing problems in the existing technology, but also significantly improve the dispersion properties of nanomaterials, providing reliable technical support for the preparation of high-performance composite graphite bipolar plates. Summary of the invention

[0014] In view of the defects of the prior art, the present invention aims to provide a wet mixing method so that nanomaterials (such as carbon nanotubes, etc.) can be evenly dispersed in the bipolar plate powder system, thereby further improving the electrical and thermal conductivity of the bipolar plate.

[0015] The present invention provides a method for preparing a fuel cell graphite composite bipolar plate with low energy consumption and high efficiency, which overcomes the technical difficulties of high energy consumption and difficult processing of graphite composite bipolar plates in the prior art.

[0016] In order to achieve this technical goal, the present invention also provides a fuel cell graphite composite bipolar plate, which is composited by flake graphite powder, worm graphite powder, synthetic resin, coupling agent and other conductive fillers.

[0017] The graphite composite bipolar plate of the present invention uses a combination of flake graphite powder and worm graphite powder as the conductive material, which significantly improves the electrical performance and stability of the bipolar plate by virtue of its excellent electrical conductivity, thermal conductivity and corrosion resistance. Worm graphite has a two-dimensional planar structure composed of a single layer of carbon atoms, and its unique crystal structure and electronic properties give it excellent electrical conductivity, thermal conductivity and mechanical properties. However, the packing density of worm graphite is relatively low, which causes the plate to expand when the compression ratio is large during processing. Relatively speaking, flake graphite not only has higher electrical conductivity and thermal conductivity, but also has a higher packing density, but its mechanical strength after pressing is slightly weaker than that of worm graphite. Therefore, the combination of the two can reduce the compression expansion rate while maintaining good mechanical properties and electrical and thermal conductivity characteristics.

[0018] In addition, synthetic resins, as binders and fillers, help improve the mechanical strength of graphite composite bipolar plates; coupling agents enhance the interfacial bonding strength between carbon materials and resins; carbon nanotubes in composite graphite bipolar plates enhance electrical and thermal conductivity, enhance current and heat conduction, improve mechanical properties and corrosion resistance, enhance the strength and stability of bipolar plates, optimize the interfacial bonding of materials, and help achieve lightweighting, thereby improving the overall performance and service life of composite bipolar plates. After these components are formed, the resulting graphite composite bipolar plates have the advantages of low gas permeability, moderate thickness, high strength, strong corrosion resistance, and low resistivity.

[0019] As a preferred solution, the mass percentage of the component raw materials is: 30-50% flake graphite powder; 10-30% worm graphite powder; 30-50% synthetic resin; 0.5-3% coupling agent; 0.2-2% chopped carbon fiber. The ratio between the raw materials of each component needs to be strictly controlled. For example, although the introduction of carbon nanotubes can improve the electrical properties of the bipolar plate, adding too much carbon nanotubes will increase the cost and processing difficulty, and may lead to excessive conductivity, decreased mechanical strength, reduced corrosion resistance, and even affect the stability of the material. Therefore, it is necessary to control the amount of addition to optimize the performance of the composite graphite bipolar plate; similarly, the ratio of graphite material to synthetic resin needs to be adjusted between balancing the mechanical properties and conductivity of the bipolar plate. If the proportion of graphite material is too low, the conductivity of the bipolar plate will be reduced; and if the proportion of synthetic resin is too low, the strength of the bipolar plate will be weakened.

[0020] As a preferred solution, the flake graphite powder has a purity of not less than 99.9% and a particle size of 300-400 meshes.

[0021] As a preferred solution, the worm graphite powder is neutral deacidified worm graphite powder with a particle size of 400-500 mesh. The preferred flake graphite powder and worm graphite powder have high electrical conductivity, high thermal conductivity and high corrosion resistance, which can give the graphite composite bipolar plate good electrical properties and stability.

[0022] As a preferred embodiment, the synthetic resin used in the present invention includes polyperfluoroethylene propylene (PFEP) and polyphenylene sulfide (PPS) resin. This resin combination can significantly improve the mechanical properties of the composite material while ensuring high temperature resistance, high corrosion resistance and good processability. A more preferred embodiment is to make polyperfluoroethylene propylene and polyphenylene sulfide resin in a mass percentage of 60-80%: 20-40%. Such a ratio combination can improve the performance of the bipolar plate while taking into account the processing convenience and cost-effectiveness of the material.

[0023] As the main component, polyperfluoroethylene propylene has excellent chemical stability and heat resistance, and is particularly suitable for applications in high temperature and highly corrosive environments. However, polyperfluoroethylene propylene has low rigidity and may not meet the high requirements of composite bipolar plates for mechanical properties when used alone. Therefore, adding an appropriate amount of polyphenylene sulfide resin can effectively improve the rigidity of polyperfluoroethylene propylene, enhance the overall mechanical strength and impact resistance of the composite material, and ensure that the bipolar plate has sufficient mechanical stability during operation. The blending ratio of polyperfluoroethylene propylene and polyphenylene sulfide has an important influence on the mechanical properties of the composite bipolar plate. If the proportion of polyphenylene sulfide is too high, the mechanical properties of the composite material may become brittle and easily break under stress or high temperature conditions; if the proportion of polyphenylene sulfide is too low, the overall mechanical properties of the composite material may be too soft, with insufficient compression and bending resistance, and cannot effectively withstand external pressure. Therefore, by reasonably adjusting the ratio of the two resins, the composite material can have both excellent chemical stability and thermal stability, and maintain good mechanical strength, and ultimately achieve ideal bipolar plate performance.

[0024] As a preferred solution, the carbon nanotubes are multi-walled carbon nanotubes with a diameter of 10 to 20 nm. The preferably used chopped carbon fibers have high strength, high modulus and low density, which can improve the mechanical properties and lightweight of the bipolar plate.

[0025] As a preferred solution, the coupling agent used is a phthalate coupling agent. The preferred coupling agent can effectively improve the interface strength between graphite, conductive filler and synthetic resin, thereby improving the mechanical properties of the entire graphite composite bipolar plate.

[0026] The present invention also provides a method for preparing a fuel cell graphite composite bipolar plate, which comprises adding component raw materials including flake graphite powder, worm graphite powder and carbon fiber into a dry mixer and mixing them evenly, then adding a coupling agent and vacuum drying under stirring to obtain a mixed powder, and then sequentially mixing the mixed powder with a synthetic resin, cold pressing and sintering to obtain the obtained product.

[0027] The preparation method of the fuel cell graphite composite bipolar plate of the present invention can realize cold pressing, mainly based on: on the one hand, by combining the use of flake graphite powder, worm graphite powder and conductive filler, the compressibility and shape stability of the material are greatly improved, and the preferred carbon-based material is easy to deform under pressure and can maintain the deformed shape, which is the basis of cold pressing. On the other hand, the introduced coupling agent can improve the compatibility between different components and enhance their bonding force. The use of the coupling agent can help form a uniform mixed powder and can be better consolidated during cold pressing. In addition, the synthetic resin plays the role of an adhesive during the mixing and cold pressing process, filling the gaps in the mixed powder, which is conducive to molding.

[0028] As a preferred solution, the molding pressure is 80-120 MPa and the molding time is 1-2 min.

[0029] As a preferred solution, the sintering conditions are: temperature of 260-400° C. and time of 1-3 hours. Sintering can further improve the density and mechanical strength of the composite bipolar plate, so that the cold-pressed bipolar plate can reach the required performance standards.

[0030] The specific preparation method of the high temperature fuel cell graphite composite bipolar plate of the present invention comprises the following steps:

[0031] (1) Preparation of PVP solution

[0032] Weigh an appropriate amount of PVP (such as 3% mass concentration), add it to deionized water or a mixed solvent, stir and heat to 40-50° C. until it is completely dissolved to obtain a uniform PVP solution.

[0033] (2) Add raw materials

[0034] Under high-speed stirring conditions, FEP resin, flake graphite, carbon nanotubes and other raw materials are gradually added in proportion to ensure stable stirring during the addition process to avoid agglomeration.

[0035] (3) Distributed processing

[0036] The mixture was stirred continuously for 5-10 minutes using a high-speed stirrer, and then subjected to ultrasonic dispersion treatment for 30 minutes to ensure that all components were evenly dispersed to form a stable dispersion system.

[0037] (4) Drying and crushing

[0038] The obtained dispersion is dried (the temperature is controlled at 60-80°C to avoid damage to the material properties) to form a dry solid material.

[0039] The dried material is crushed by a mechanical pulverizer to obtain fine particle powder.

[0040] (5) Screening

[0041] The crushed powder is sieved (the sieve size is selected according to the target particle size, such as 100-200 mesh), and large particles are removed to obtain a uniform powder.

[0042] The graphite / carbon fiber / coupling agent / synthetic resin mixture in step (4) is molded at a pressure of 80 to 120 MPa for a time of 1 to 5 minutes to obtain a cold-pressed prefabricated plate of the desired bipolar plate;

[0043] (6) Cold Pressing

[0044] The sieved powder is placed in a cold press mold and pressed under appropriate pressure (such as 100-120 MPa) to form a preliminary blank.

[0045] (7) Sintering treatment

[0046] The cold-pressed blank is placed in a sintering furnace and sintered according to a preset temperature curve (eg, 260-400° C., depending on the requirements of the FEP and graphite system) to obtain a final product.

[0047] Compared with the prior art, the advantages and effects brought by the technical solution of the present invention are:

[0048] (1) Excellent dispersibility and uniformity

[0049] Through high-speed stirring and ultrasonic dispersion treatment, each component (such as FEP resin, flake graphite, carbon nanotubes, etc.) is evenly dispersed to avoid agglomeration, thereby improving the overall performance of the composite material. This uniform dispersion system helps to improve the electrical conductivity, thermal conductivity and mechanical properties of the bipolar plate. Dispersion effect such as Figure 1 Shown

[0050] (2) Improve the stability of materials

[0051] During the dispersion process, ultrasonic dispersion technology is used to fully disperse the components in the solution to form a stable dispersion system, avoiding the performance fluctuations caused by material agglomeration in traditional methods. This stability plays an important role in the performance of the final composite material, especially in applications under high temperature and high pressure environments.

[0052] (3) Gentle drying and crushing process

[0053] The drying process is controlled at a temperature of 60-80°C to avoid the damage to the material properties caused by excessively high temperatures and maintain the best performance of the raw materials. The mechanical crushing process effectively converts the dry solid materials into fine-grained powder, ensuring the uniformity of the powder and its suitability for subsequent cold pressing.

[0054] (4) Efficient cold pressing

[0055] In the cold pressing step, a pressure of 80-120 MPa is used to complete the initial forming of the bipolar plate in a short time (1-5 minutes), ensuring the high efficiency of the forming process and good surface quality, and avoiding the uneven forming or defect problems that may occur in traditional methods. Figure 2 Shown

[0056] (5) Accurate sintering control

[0057] The temperature during the sintering process is controlled within the range of 260-400°C, which can be precisely controlled according to the requirements of FEP resin and graphite to ensure the sintering quality and final performance of the composite material. This sintering process can effectively improve the strength, corrosion resistance, thermal stability and other key properties of the composite material to meet the requirements of high-temperature fuel cell bipolar plates.

[0058] (6) Optimized material combination

[0059] The use of a variety of high-quality raw materials such as flake graphite, FEP resin, carbon nanotubes, etc., and through a reasonable proportion and process combination, the electrical conductivity, thermal conductivity, mechanical strength and corrosion resistance of the bipolar plate are improved. The addition of carbon nanotubes further improves the electrical conductivity and enhances the overall performance, making the bipolar plate more stable and reliable.

[0060] (7) Environmental protection and economy

[0061] The solvents and raw materials used in this method are more environmentally friendly. At the same time, through processing steps such as cold pressing and sintering, the high energy consumption and waste generation in the traditional production process are reduced. Compared with the existing technology, the manufacturing process is simpler, more efficient and has better economic efficiency.

[0062] (8) Customizable performance adjustments

[0063] By adjusting the ratio of FEP resin to flake graphite, carbon nanotubes and other materials, as well as the process parameters of sintering and cold pressing, the properties of the bipolar plate, such as electrical conductivity, thermal conductivity, mechanical strength and corrosion resistance, can be precisely adjusted. This high degree of adjustability enables the preparation method to be optimized according to the needs of different fuel cells and has strong adaptability. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] Figure 1 This is a diagram of the dispersion effect of the composite material;

[0065] Figure 2 This is a cross-sectional view of the composite graphite bipolar plate involved in this patent. DETAILED DESCRIPTION

[0066] The following specific examples are intended to further illustrate the present invention, rather than to limit the scope of protection of the claims of the present invention.

[0067] In the following specific embodiments, the PVP used is PVP-K15, produced by Guangdong Yuemei Chemical Co., Ltd., polyphenylene sulfide is produced by Dongguan Zhangmutou Hengtai Plastics, etc., with a mesh size of 1000 mesh; the polyperfluoroethylene propylene used is Daikin 1101, with a mesh size of 2000 mesh. The flake graphite powder used has a purity of 99.9% and a particle size of 300 mesh. The worm graphite powder used is neutral deacidified worm graphite powder with a particle size of 400 mesh.

[0068] Example 1

[0069] (1) Preparation of PVP solution: Weigh an appropriate amount of PVP (3% mass concentration), add it into deionized water, stir and heat to 40° C. until it is completely dissolved to obtain a uniform PVP solution.

[0070] (2) Adding raw materials: under high-speed stirring conditions, add carbon nanotubes, FEP resin, PPS resin, worm graphite, and flake graphite in order according to a weight ratio of 1:20:10:30:40.

[0071] (3) Dispersion treatment: Use a high-speed stirrer to stir continuously for 5 minutes, and then use an ultrasonic disperser for 30 minutes to ensure that all components are evenly dispersed to form a stable dispersion system.

[0072] (4) Drying and crushing: The dispersion was dried at 60°C to obtain a solid material, which was then crushed into fine particles using a mechanical crusher.

[0073] (5) Screening: The crushed powder is screened with a sieve size of 150 mesh to remove large particles and obtain a uniform powder.

[0074] (6) Cold pressing: The sieved powder is placed in a cold press mold and pressed at a pressure of 100 MPa and a holding time of 30 s to obtain a preliminary blank.

[0075] (7) Sintering treatment: The cold-pressed blank is placed in a sintering furnace and sintered according to a temperature curve (320°C, insulation for 2 hours) to obtain the final graphite composite bipolar plate.

[0076] Example 2

[0077] The difference from Example 1 is that: the concentration of the PVP solution in step (1) is 1%, and other conditions remain unchanged;

[0078] Example 3

[0079] The difference from Example 1 is that: in step (2), a phthalate coupling agent accounting for 1% by weight of the powder is added before adding the raw materials, and the other conditions remain unchanged;

[0080] Example 4

[0081] The difference from Example 1 is that: in step (2), a phthalate coupling agent accounting for 2% by weight of the powder is added before adding the raw materials, and the other conditions remain unchanged;

[0082] Example 5

[0083] The difference from Example 1 is that the material ratio in step (2) is changed to carbon nanotubes: FEP resin: PPS resin: worm graphite: flake graphite = 2:20:10:30:40; other conditions remain unchanged;

[0084] Example 6

[0085] The difference from Example 1 is that the material ratio in step (2) is changed to carbon nanotubes: FEP resin: PPS resin: worm graphite: flake graphite = 1:25:15:20:40; other conditions remain unchanged;

[0086] Example 7

[0087] The difference from Example 1 is that the material ratio in step (2) is changed to carbon nanotubes: FEP resin: PPS resin: worm graphite: flake graphite = 1:15:10:25:50; other conditions remain unchanged;

[0088] Example 8

[0089] The difference from Example 1 is that the material ratio in step (2) is changed to carbon nanotubes: FEP resin: PPS resin: worm graphite: flake graphite = 1:10:20:30:40; other conditions remain unchanged;

[0090] Example 9

[0091] The difference from Example 1 is that the molding pressure in step (6) is 90 MPa and the molding time is 1 minute, the sintering temperature in step (7) is 340°C and the sintering time is 2 hours, and the remaining steps are the same as Example 1.

[0092] Example 10

[0093] The difference from Example 1 is that the molding pressure in step (6) is 100 MPa and the molding time is 2 minutes; in step (7), the sintering temperature is 340°C and the sintering time is 1.5 hours; the remaining steps are the same as Example 1.

[0094] Comparative Example 1

[0095] The difference from Example 1 is that: in step (2), no carbon nanotubes are added, and the mixing method is to mix all the powders by ball milling for 2 hours at a speed of 300 RPM, and then the mixed powder is directly pressed;

[0096] Comparative Example 2

[0097] The difference from Example 1 is that the resin in step (2) is polyperfluoroethylene propylene (without adding polyphenylene sulfide, and the total amount of resin is consistent with that in Example 1), and the remaining steps are the same as those in Example 1.

[0098] Table 1 The performance test results of the above embodiments 1 to 10 and comparative embodiments 1 to 2 are as follows:

[0099]

[0100]

Claims

1. A method for preparing a composite graphite bipolar plate by a wet mixing method, characterized in that: The following steps are involved: (1) Prepare PVP solution by mixing PVP with deionized water or mixed solvent, stirring and heating to 40-50°C until completely dissolved; (2) under high-speed stirring conditions, gradually add flake graphite powder, worm graphite powder, carbon nanotubes and other raw materials to ensure uniform stirring during the addition process to avoid agglomeration; (3) subjecting the mixture to ultrasonic dispersion treatment to ensure that the components are evenly dispersed to form a stable dispersion system; (4) drying the obtained dispersion and controlling the temperature at 60-80° C. to avoid damage to the material properties; (5) mechanically crushing the dried solid material to obtain fine particle powder; (6) After sieving, a uniform powder is obtained; (7) cold pressing to press the powder into a shape at a pressure of 80 to 120 MPa; (8) Sintering treatment is performed to sinter the cold-pressed blank at 260 to 400° C. for 1 to 3 hours to obtain a final composite graphite bipolar plate.

2. The method for preparing composite graphite bipolar plates by wet mixing according to claim 1, characterized in that: The flake graphite powder has a purity of not less than 99.9% and a particle size of 300-400 meshes. The worm graphite powder is neutral deacidified worm graphite powder and has a particle size of 400-500 meshes.

3. The method for preparing composite graphite bipolar plates by wet mixing according to claim 1, characterized in that: The synthetic resin comprises polyperfluoroethylene propylene (PFEP) and polyphenylene sulfide (PPS) resin, and the resins are combined in a mass percentage of 60-80%:20-40%.

4. The method for preparing composite graphite bipolar plates by wet mixing according to claim 1, characterized in that: The carbon nanotubes are multi-walled carbon nanotubes with a diameter of 10 to 20 nm.

5. The method for preparing composite graphite bipolar plates by wet mixing according to claim 1, characterized in that: The coupling agent is a phthalate coupling agent.

6. The method for preparing composite graphite bipolar plates by wet mixing according to claim 1, characterized in that: The pressure during the cold pressing is 80-120 MPa and the time is 1-2 minutes.

7. The method for preparing composite graphite bipolar plates by wet mixing according to claim 1, characterized in that: The sintering conditions are: temperature of 260-400° C. and time of 1-3 hours.

8. A fuel cell graphite composite bipolar plate prepared by the method according to any one of claims 1 to 7, characterized in that: The bipolar plate has low gas permeability, high strength, good corrosion resistance, low resistivity, and excellent electrical and thermal conductivity.